(untitled) (Revista de Ciências Agroveterinárias, 2023)
Coffee crop has been growing increasingly in Brazil and, in view of this, technologies are constantly being developed to obtain greater productivity. In this context, the effect of polyethylene mulching as a source of fertilizer on coffee production has been studied. The objective of this work was to evaluate the incidence of leaf miner and red mite in coffee as a function of the use of polyethylene mulching and controlled and conventional release fertilizer. The research was carried out in the experimental area of ​​the Federal University of Uberlândia - Campus Monte Carmelo, Minas Gerais, with the cultivar IPR 100, in a randomized block design with four blocks. The following treatments were tested: T1 - double-faced white/black mulching with conventional fertilizer; T2 – white/black double-sided mulching with controlled release fertilizer; T3 – double-sided silver/black mulching with conventional fertilizer; T4 – silver/black double-sided mulching with controlled release fertilizer; T5 – No mulching with conventional fertilizer; T6 – No mulching with controlled release fertilizer. The evaluations took place fortnightly from July 2020 to December 2020, upon verification of the presence or absence of leaf miner and red mite caterpillars. Population density peaks for leaf miner occurred from July to October 2020, and for red mite in August, due to low relative humidity and precipitation. Thus, it is concluded that the use of double-sided silver/black mulching provided greater attractiveness to the coffee leaf miner. The fertilizer sources did not influence the probability of occurrence of this insect pest. In addition, conventional fertilizers, as well as those of controlled release, and the absence/presence of soil coverings, did not influence the incidence of red mite in coffee trees in the Cerrado Mineiro region.